2019
DOI: 10.1038/s41598-019-56021-w
|View full text |Cite
|
Sign up to set email alerts
|

Controlling properties of human neural progenitor cells using 2D and 3D conductive polymer scaffolds

Abstract: Human induced pluripotent stem cell-derived neural progenitor cells (hNPCs) are a promising cell source for stem cell transplantation to treat neurological diseases such as stroke and peripheral nerve injuries. However, there have been limited studies investigating how the dimensionality of the physical and electrical microenvironment affects hNPC function. In this study, we report the fabrication of two- and three-dimensional (2D and 3D respectively) constructs composed of a conductive polymer to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 94 publications
(109 reference statements)
0
46
0
Order By: Relevance
“…Previous studies demonstrated that a single 1 h period of electrical stimulation results in sustained alteration of progenitor cell gene expression. [ 22,38 ] Utilizing these parameters for duration of stimulation, the voltage for electrical stimulation of the iPSCs was optimized by assessing neuronal differentiation from iPSCs for CGS stiffness (elasticity ranging from 3 to 12 kPa) and voltage (applied voltages ranging ±100 mV to ±3 V) ( Figure A; Figure S3 and Table S1, Supporting Information). Exposure to ±800 mV at 100 Hz for 1 h on the soft CGS (≈3 kPa) significantly increased the generation of TUJ1 + neurons without adverse cytotoxicity after 7d culture on the CGSs (Figure S3A–D and Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that a single 1 h period of electrical stimulation results in sustained alteration of progenitor cell gene expression. [ 22,38 ] Utilizing these parameters for duration of stimulation, the voltage for electrical stimulation of the iPSCs was optimized by assessing neuronal differentiation from iPSCs for CGS stiffness (elasticity ranging from 3 to 12 kPa) and voltage (applied voltages ranging ±100 mV to ±3 V) ( Figure A; Figure S3 and Table S1, Supporting Information). Exposure to ±800 mV at 100 Hz for 1 h on the soft CGS (≈3 kPa) significantly increased the generation of TUJ1 + neurons without adverse cytotoxicity after 7d culture on the CGSs (Figure S3A–D and Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…These results further support prior studies which indicate that electrical stimulation can alter gene expression in progenitor cells and are a key mechanism for downstream effects. [ 22,38,39 ]…”
Section: Resultsmentioning
confidence: 99%
“…Electrical stimulation of hydrogel-immobilized hNPCs alters hNPCs genes involved in metabolic pathways and cell proliferation upregulates neurotrophic factors correlated with nerve regeneration, synaptic remodeling, and cell survival. These findings indicate that electrical stimulation modifies hNPC properties and may be beneficial to provide a novel therapy for neurological disease [ 173 ].…”
Section: Remodeling Of the Stroke Tissue Microenvironment Within The Brainmentioning
confidence: 99%
“…Electrical stimulation enhances cell proliferation, migration, differentiation, and signaling connections between nerve cells, thereby enhancing neural regeneration and supporting the differentiation of stem cells into nerve cells [119,120]. Polypyrrole (PPy) [121,122], polyaniline (PANI) [123], poly (3,4-ethylenedioxythiophene) (PEDOT) [124,125] are the most promising conductive polymers for tissue engineering [126]. Many researchers indicated that conductive materials show good biocompatibility when co-cultured with cells in vitro [127].…”
Section: Conductive Polymersmentioning
confidence: 99%